What the Seasons Tell Us. The Monthly Movement of Marriages, Economic Modernization, and Secularization in the Netherlands, 1810-1940 - Theo Engelen (Historical Life Course Studies)
This study focuses on the seasonal pattern of marriages in seven provinces of the Netherlands from 1810 to 1940. We ask whether the prevalence of May as the preferred marriage month was diminishing when industrialization changed the course of workload over the year. And if so, when did this occur, and were there differences between the regions? Given the ban on marriages during Lent and Advent, by studying the number of marriages during these months (approximated as March and December), we can determine which provinces adhered most to the religious rules, and how this pattern developed over time. In doing so, we have an excellent demographic measure for secularization. The analysis is based on the LINKS dataset which currently includes almost 2 million marriages that were contracted in seven Dutch provinces: Groningen, Drenthe, Overijssel, Gelderland, Noord-Holland, Zeeland and Limburg. The main conclusion of this study is that although Dutch society substantially transformed (economically, socially, politically and culturally) during the 19th and early 20th centuries until the Second World War, it was both the agricultural calendar and the Roman Catholic regulations that determined Dutch marriage seasonality.